Cancer Stem Cells: Emerging Key Players in Immune Evasion of Cancers - Lei, Martina Mang Leng; Lee, Terence Kin Wah (Frontiers in Cell and Developmental Biology, 2021)
Cancer stem cells (CSCs) are subpopulations of undifferentiated cancer cells within the tumor bulk that are responsible for tumor initiation, recurrence and therapeutic resistance. The enhanced ability of CSCs to give rise to new tumors suggests potential roles of these cells in the evasion of immune surveillance. A growing body of evidence has described the interplay between CSCs and immune cells within the tumor microenvironment (TME). Recent data have shown the pivotal role of some major immune cells in driving the expansion of CSCs, which concurrently elicit evasion of the detection and destruction of various immune cells through a number of distinct mechanisms. Here, we will discuss the role of immune cells in driving the stemness of cancer cells and provide evidence of how CSCs evade immune surveillance by exerting their effects on tumor-associated macrophages (TAMs), dendritic cells (DCs), myeloid-derived suppressor cells (MDSCs), T-regulatory (Treg) cells, natural killer (NK) cells, and tumor-infiltrating lymphocytes (TILs). The knowledge gained from the interaction between CSCs and various immune cells will provide insight into the mechanisms by which tumors evade immune surveillance. In conclusion, CSC-targeted immunotherapy emerges as a novel immunotherapy strategy against cancer by disrupting the interaction between immune cells and CSCs in the TME.